Earnings quality at initial public offerings - Ball, Ray; Shivakumar, Lakshmanan (Journal of Accounting and Economics, 2008)
We show that, contrary to popular belief, initial public offering (IPO) firms report more conservatively. We attribute this to the higher quality reporting demanded of public firms by financial statement users and consequentially higher monitoring by auditors, boards, analysts, rating agencies, press, and litigants, and to greater regulatory scrutiny [Ball, R., Shivakumar, L., 2005. Earnings quality in UK private firms: comparative loss recognition timeliness. Journal of Accounting and Economics 39, 83–128]. We also question the evidence of Teoh et al. [1998b. Earnings management and the subsequent market performance of initial public offerings. Journal of Finance 53, 1935–1974] supporting the alternative hypothesis that managers opportunistically inflate earnings to influence IPO pricing. We conjecture that upward-biased estimates of “discretionary” accruals occur in a broad genre of studies on earnings management around similar large transactions and events.